The Role of Digital Platforms in Increasing MSME’s Sales - Fahrudin Pasolo; Mohammad Aldrin Akbar; Entar Sutisman; Imaduddin Imaduddin (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to find out why MSMEs use Digital Platforms in marketing their products and identify what factors influence the sales of MSME products. The location in this study is in the city of Makassar, precisely in the MSME sector. Criteria for selecting informants in phenomenological research include that the informant must directly experience situations or events related to the research topic. This study uses descriptive qualitative research methodology and SWOT analysis techniques. The result showed that MSMEs in Makassar City have carried out the four stages of marketing strategy well and experienced an increase in consumer interest. Based on the SWOT analysis, it can be concluded that the opportunity to use social media for selling MSME products can have an effect if it is done optimally in terms of the length of time for promotion and the development of marketing strategies such as increasing product creativity so that the products offered are more variated. In terms of marketing, optimizing social media to improve marketing relationship networks and allocating funds to improve information technology to facilitate product marketing, for example, placing paid digital advertisements on social media, which can expand market share. Digital advertising is more effective and cheaper than traditional advertising.